Identification of a New DNA Region Specific for Members of Mycobacterium tuberculosis Complex - Magdalena, Juana (American Society for Microbiology, 1998)
The successful use of DNA amplification for the detection of tuberculous mycobacteria crucially depends on the choice of the target sequence, which ideally should be present in all tuberculous mycobacteria and absent from all other bacteria. In the present study we developed a PCR procedure based on the intergenic region (IR) separating two genes encoding a recently identified mycobacterial two-component system named SenX3-RegX3. The senX3-regX3 IR is composed of a novel type of repetitive sequence, called mycobacterial interspersed repetitive units (MIRUs). In a survey of 116 Mycobacterium tuberculosis strains characterized by different IS6110 restriction fragment length polymorphisms, 2 Mycobacterium africanum strains, 3 Mycobacterium bovis strains (including 2 BCG strains), and 1 Mycobacterium microti strain, a specific PCR fragment was amplified in all cases. This collection included M. tuberculosis strains that lack IS6110 or mtp40, two target sequences that have previously been used for the detection of M. tuberculosis. No PCR fragment was amplified when DNA from other organisms was used, giving a sensitivity of 100% and a specificity of 100% in the confidence limit of this study. The numbers of MIRUs were found to vary among strains, resulting in six different groups of strains on the basis of the size of the amplified PCR fragment. However, the vast majority of the strains (approximately 90%) fell within the same group, containing two 77-bp MIRUs followed by one 53-bp MIRU.